2011
DOI: 10.1163/138855410x517048
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Kaempferia galanga rhizome constituents to Meloidogyne incognita juveniles and eggs

Abstract: The toxicity of Kaempferia galanga rhizome constituents to second-stage juveniles (J2) and eggs of Meloidogyne incognita was examined in vitro and in container experiments. Results were compared with those of three nematicides: carbofuran, fosthiazate and metam sodium. Ethyl cinnamate (EC) and ethyl p-methoxycinnamate (EMC) were the nematicidal and hatch inhibitory principles. In direct-contact mortality bioassays, EC (0.037 mg ml −1 ) and EMC (0.041 mg ml −1 ) were more toxic than carbofuran (0.092 mg ml −1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…White needle, C-11). The data matched with previous reports [14,18]. [27], and Valeriana amurensis (311.6 μg/mL) [22].…”
Section: 8-cineolesupporting
confidence: 91%
See 2 more Smart Citations
“…White needle, C-11). The data matched with previous reports [14,18]. [27], and Valeriana amurensis (311.6 μg/mL) [22].…”
Section: 8-cineolesupporting
confidence: 91%
“…It is suggested that acute toxicity of the essential oil of K. galanga rhizomes maybe attributed to the three cinnamate derivatives (ethyl ρ-methoxy cinnamate, trans-cinnamaldehyde, ethyl cinnamate). Moreover, in the previous reports, the three cinnamate derivatives (ethyl ρ-methoxy cinnamate, trans-cinnamaldehyde, ethyl cinnamate) were revealed to exhibit nematicidal activity against the pine wood nematode, B. xylophilus and the southern root-knot nematode, M. incognita [18,28,29].…”
Section: 8-cineolementioning
confidence: 94%
See 1 more Smart Citation
“…At a dose of 62 µg/ml, ethylcinnamate shows 100% hatch inhibition; however ethyl-pmethoxycinnamate shows 81% hatch inhibition that rises to a maximum of 93% at a dose of 125 µg/ml. This hatch inhibition dose is lesser (more efficient) than carbofuran and metham sodium (Hong et al, 2011). Hong et al (2011) have further demonstrated that the efficiency of ethyl-cinnamate and ethyl-p-methoxycinnamate in steam phase mortality bioassay is greater in closed container than in open container which suggests that mode of delivery of these constituents is partly through vapour phase.…”
Section: Anti-inflammatory and Analgesic Activitymentioning
confidence: 85%
“…The capacity of the extracts to block abdominal constriction, hot plate and formaline test indicates that analgesic activity has both central mechanism, involving opioid receptors, and peripheral mechanism that involves cyclooxygenase pathway (Ridtitid et al, 2008;Sulaiman et al, 2008). incognita is 37 and 41 µg/ml, respectively that is greater than Carbofuran (92 µg/ml) but lesser than fosthiazate (2 µg/ml) (Hong et al, 2011). At a dose of 62 µg/ml, ethylcinnamate shows 100% hatch inhibition; however ethyl-pmethoxycinnamate shows 81% hatch inhibition that rises to a maximum of 93% at a dose of 125 µg/ml.…”
Section: Anti-inflammatory and Analgesic Activitymentioning
confidence: 99%